Sixth graders' co-construction of explanations of a disturbance in an ecosystem: exploring relationships between grouping, reflective scaffolding, and evidence-based explanations - Spanoudis, George; Constantinou, Constantinos P.; Kyza, Eleni A. (My University, 2011)
We report on a study investigating the relationship between cognitive ability grouping, reflective inquiry scaffolding, and students' collaborative explanations of an ecosystem disturbance which took place when a number of flamingo birds died in a salt lake because of nearby intensive human activities. Twenty-six pairs of students from two intact sixth-grade classes participated in the study. All students investigated scientific data relating to the ecosystem problem using a web-based learning environment. One class was provided with web-based reflective inquiry scaffolding (WorkSpace), while the other class used PowerPoint. The main data analyzed for this study consisted of each pair's written explanation and task-related artifacts. Findings show that the web-based reflective scaffolding supported students in providing valid evidence in support of their explanations. The analyses of the students' collaborative explanations showed no statistically significant differences that could be attributed to prior achievement between students in the WorkSpace condition, while differences were found between the different cognitive ability pairs in the PowerPoint class. These findings suggest that the WorkSpace scaffolding may have provided more influential support to lower cognitive ability pairs in creating evidence-based explanations.
Keywords: Evidence-based reasoning; Explanations; Inquiry-based learning; Reflective inquiry scaffolding